Penggunaan Media Gambar Untuk Meningkatkan Hasil Belajar Siswa SD - Mai Sri Lena; Sartono Sartono; Annisa Salsabila; Wulan Mulyani (Badan Penerbit STIEPARI Press, 2023)
.The purpose of this study is to find out how the role of the image media is to improve the learning outcomes of elementary school students. This study is a descriptive quantitative study. The study time was in April 2023 and took approximately 2 weeks. The subject of this study is elementary school teachers in Bukittinggi. Research is conducted by formulating research problems, tracing the research results of relevant and similar journals for analysis of their data. The benefits of image media are the explanation and delivery of various information, messages, ideas, and so on by giving the impression of being visible using verbal language. Based on the results, studies have shown teachers agree that the use of image media in the learning process can improve students' learning outcomes. Because more than 50% to 60% of respondents agreed to this.